Hydroxymethylation is uniquely distributed within term placenta, and is associated with gene expression. Issue 8 (26th April 2016) - Green, Benjamin B.; Houseman, E. Andres; Johnson, Kevin C.; Guerin, Dylan J.; Armstrong, David A.; Christensen, Brock C.; Marsit, Carmen J.
ABSTRACT: The conversion of cytosine to 5‐methylcystosine (5mC) is an important regulator of gene expression. 5mC may be enzymatically converted to 5‐hydroxymethylcytosine (5hmC), with a potentially distinct regulatory function. We sought to investigate these cytosine modifications and their effect on gene expression by parallel processing of genomic DNA using bisulfite and oxidative bisulfite conversion in conjunction with RNA sequencing. Although values of 5hmC across the placental genome were generally low, we identified 21, 000 loci with consistently elevated levels of 5‐hydroxymethycytosine. Absence of 5hmC was observed in CpG islands and, to a greater extent, in non‐CpG island‐associated regions. 5hmC was enriched within poised enhancers, and depleted within active enhancers, as defined by H3K27ac and H3K4me1 measurements. 5hmC and 5mC were significantly elevated in transcriptionally silent genes when compared with actively transcribed genes. 5hmC was positively associated with transcription in actively transcribed genes only. Our data suggest that dynamic cytosine regulation, associated with transcription, provides the most complete epigenomic landscape of the human placenta, and will be useful for future studies of the placental epigenome.—Green, B. B., Houseman, E. A., Johnson, K. C., Guerin, D. J., Armstrong, D. A., Christensen, B. C., Marsit, C. J. Hydroxymethylation is uniquely distributed within term placenta, and is associated with gene expression. FASEB J. 30, 2874‐2884 (2016). www.fasebj.org